Stomatal Closure and Rise in ROS/NO of Arabidopsis Guard Cells by Tobacco Microbial Elicitors: Cryptogein and Harpin - Gayatri, Gunja; Agurla, Srinivas; Kuchitsu, Kazuyuki; Anil, Kondreddy; Podile, Appa R.; Raghavendra, Agepati S. (Frontiers in Plant Science, 2017)
Plants use stomatal closure mediated by elicitors as the first step of the innate immune response to restrict the microbial entry. We present a comprehensive study of the effect of cryptogein and harpin, two elicitors from microbial pathogens of tobacco, on stomatal closure and guard cell signaling components in Arabidopsis thaliana, a model plant. Cryptogein as well as harpin induced stomatal closure, while elevating the levels of reactive oxygen species (ROS) and nitric oxide (NO) in the guard cells of A. thaliana. Kinetic studies with fluorescent dyes revealed that the rise in ROS levels preceded that of NO in guard cells, when treated with these two elicitors. The restriction of NO levels in guard cells, even by ROS modulators indicates the essentiality of ROS for NO production during elicitor-triggered stomatal closure. The signaling events during elicitor-induced stomatal closure appear to converge at NADPH oxidase and ROS production. Our results provide the first report on stomatal closure associated with rise in ROS/NO of guard cells by cryptogein and harpin in A. thaliana. Our results establish that A. thaliana can be used to study stomatal responses to the typical elicitors from microbial pathogens of other plants. The suitability of Arabidopsis opens up an excellent scope for further studies on signaling events leading to stomatal closure by microbial elicitors.